The Use of Blended Diets in Children With Enteral Feeding Tubes: A Joint Position Paper of the ESPGHAN Committees of Allied Health Professionals and Nutrition. Issue 1 (2nd January 2023) - Köglmeier, Jutta; Assecaira, Ines; Banci, Elena; De Koning, Barbara; Haiden, Nadja; Indrio, Flavia; Kastelijn, Wendy; Kennedy, Denise; Luque, Veronica; Norsa, Lorenzo; Verduci, Elvira; Sugar, Analou
Abstract : Objectives: This joint position paper of the Committees of Allied Health Professionals (CAHP) and Nutrition (CON) of the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) provides a comprehensive guide for health professionals to manage blended diets in children via gastrostomy tubes. Methods: A systematic literature search was performed from 1992 to 2021 using Pubmed, MEDLINE, and Cochrane Database of Systematic Reviews and recent guidelines reviewed. In the absence of evidence, recommendations reflect the authors' expert opinion. Final consensus was obtained by multiple e-mail exchange and virtual meetings of the CAHP and CON. Results: Reported benefits of blended diets include reduced GERD and infections, improved defecation, level of alertness and attention span, skin conditions, and appearance of hair and nails. Families report a sense of greater normality. Small case series, cross-sectional surveys, questionnaire-based small case studies, reports of personal experience, and single-center pilot studies are available in the medical literature. A total of 20 recommendations for practice were made based on the results and consensus process. Conclusions: There is little evidence published to formally inform about the potential health benefits or risks of this practice and how to use it in the best way. This leaves health professionals caring for such patients in a relative vacuum regarding what to consider when providing a duty of care to patients and carers who wish to pursue this method of feeding. This article provides guidelines for safe and appropriate use of a BD, but more research is needed.